2020
DOI: 10.3892/etm.2020.8711
|View full text |Cite
|
Sign up to set email alerts
|

gga‑microRNA‑375 negatively regulates the cell cycle and proliferation by targeting Yes‑associated protein 1 in DF‑1 cells

Abstract: MicroRNAs (miRNAs/miRs) serve a key role in regulating the cell cycle and inducing tumorigenesis. Subgroup J of the avian leukosis virus (ALV-J) belongs to the family Retroviridae, subfamily Orthoretrovirinae and genus Alpharetrovirus that causes tumors in susceptible chickens. gga-miR-375 is downregulated and Yes-associated protein 1 (YAP1) is upregulated in ALV-J-induced tumors in the livers of chickens, and it has been further identified that YAP1 is the direct target gene of gga-miR-375. In the present stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…However, those 31 miRNAs were not only identified in the ZS-1 samples, but also in the primary and the 21st passage CEF samples. Another study reported that gga-miR-375 was identified in the DF-1 cells ( Zhang et al., 2020b ), which was identified in the primary CEF and the ZS-1 samples ( Supplementary Table S4 ), but not in the 21st passage CEF samples. By comparing the 3 lists of identified miRNAs of the 3 types of cell samples, a total of 42 miRNAs (18 known and 24 novel miRNAs) was found present only on the list of the primary CEF samples; 5 novel miRNAs were identified only in the 21st passage CEF samples; and a set of different 5 novel miRNAs was detected only in the ZS-1 cells.…”
Section: Resultsmentioning
confidence: 99%
“…However, those 31 miRNAs were not only identified in the ZS-1 samples, but also in the primary and the 21st passage CEF samples. Another study reported that gga-miR-375 was identified in the DF-1 cells ( Zhang et al., 2020b ), which was identified in the primary CEF and the ZS-1 samples ( Supplementary Table S4 ), but not in the 21st passage CEF samples. By comparing the 3 lists of identified miRNAs of the 3 types of cell samples, a total of 42 miRNAs (18 known and 24 novel miRNAs) was found present only on the list of the primary CEF samples; 5 novel miRNAs were identified only in the 21st passage CEF samples; and a set of different 5 novel miRNAs was detected only in the ZS-1 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Further, co-infection of reticuloendotheliosis virus (REV) and avian leukosis virus subgroup J (ALV-J) in vitro promotes viral replication by synergistically increasing exosomal miRNAs (miR-184-3p, miR-146a-3p, miR-146a-5p, miR-3538, and miR-155). Further, the downregulation of gga-miR-375 and the upregulation of YAP1 caused by ALV-J infection affect the cell cycle, leading to tumor formation ( 75 ). Together, these studies contribute to our understanding of the complex relationship between miRNAs and ALV infections and provide potential targets to control ALV-associated diseases in chickens.…”
Section: Mirnas Involved In Poultry Diseasesmentioning
confidence: 99%
“…Gga-miR-221 deregulates the G1/S transition by targeting cyclin-dependent kinase inhibitor 1B (CDKN1B), promoting cell proliferation and cell cycle progression ( 61 ). Gga-miR-375 and gga-miR-148A-5p could inhibit cell proliferation by targeting Yes-associated protein 1 (YAP1) and PDPK1, respectively ( 62 64 ). Several viruses were found to encode miRNAs, targeting cellular or viral mRNAs to promote an intracellular environment favorable to the completion of the viral life cycle ( 65 ).…”
Section: Cellular Factors Affecting Alv Replicationmentioning
confidence: 99%
“…Upon ALV-J infection, gga-miR-375 was significantly down-regulated, while circ-Vav3 was up-regulated. The circ-Vav3/gga-miR-375 and its target YAP1 induces epithelial-mesenchymal transition (EMT) through influencing EMT markers to promote tumorigenesis ( 62 , 63 ). The non-coding RNAs play multiple roles in ALV replication.…”
Section: Cellular Factors Affecting Alv Replicationmentioning
confidence: 99%